Strategi Komunikasi PT. JMTO Pondok Ranji Melalui Media Instagram Dalam Menginformasikan Rencana Kebijakan Penggunaan MLFF - Atik; Iin Soraya; Sari Ekowati Hadi (CV Edujavare Publishing, 2024)
Economic competition in the business sector is getting fiercer. For a business to be successful, companies must sell their products using company-defined strategies and high-quality products. There are several ways to achieve marketing targets, one of which is to have a strong strategy. This study uses a type of descriptive qualitative research method. This research was conducted by means of observation, interviews, and documentation. The researcher met the informant directly with the aim of obtaining detailed results about the communication strategy of PT. JMTO Pondok Ranji through Instagram media in informing the policy for the preparation of the MLFF plan. Based on the results of the research obtained through in-depth interviews with four interviewees, the researcher wanted to find out how to communicate in the company being studied. The results of the interview obtained are then processed from communication strategies, delivery and produce answers to the problem formulation that has been made before. The activity of sharing stories or Instagram feeds is very helpful for PT JMTO in conveying information about mlff or other information about activities and promotions about products owned by PT JMTO. The communication strategy that has been explained earlier has also been interacted with directly, through Instagram. Direct interaction is carried out by PT JMTO with followers on the account. Direct interaction on Instagram is by replying to messages sent via direct message, replying to comments in the comment column of Instagram feed posts and other things that are active on Instagram. The strategy in this way will be easier for PT JMTO to convey information and more effective with followers on its Instagram account.